KAJIAN ASPEK FINANSIAL INDUSTRI MINUMAN BUBUK KUNYIT ASAM - Satriawan, I Ketut; Mulyani, Sri (Universitas Udayana, 2007)
Beverage of “kunyit-asam” was being familiar in the society as a traditional herbs, fresh beverage, and potential antioxidant. However, it’s industry not yet much done in home industry scale.This research aimed to evaluate investment value which needed and financial feasibility of “kunyit-asam” powderindustry in home industry scale. The analysis which used in financial feasibility i.e. : Net Present Value (NPV), InternalRate of Return (IRR), Pay Back Period (PBP), Break EvenPoint (BEP), Net Benefit-Cost Ratio (Net B/C), and sensitivityanalysis.Investment value which needed for planning of “kunyit-asam” powder industry in home industry scale is Rp. 52.364.065. The analysis of financial feasibility of “kunyit-asam” powder industry in home industry scale is feasible based on some value of investment criteria.